(untitled) (Journal of Computational Mathematics, 2018)
In this paper, a nonmonotone method based on McCormick's second-order Armijo's step-size rule [7] for unconstrained optimization problems is proposed. Every limit point of the sequence generated by using this procedure is proved to be a stationary point with the second-order optimality conditions. Numerical tests on a set of standard test problems are presented and show that the new algorithm is efficient and robust.